2014
DOI: 10.1016/j.meegid.2014.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Towards a phylogenetic approach to the composition of species complexes in the North and Central American Triatoma, vectors of Chagas disease

Abstract: Phylogenetic relationships of insect vectors of parasitic diseases are important for understanding the evolution of epidemiologically relevant traits, and may be useful in vector control. The subfamily Triatominae (Hemiptera:Reduviidae) includes ~140 extant species arranged in five tribes comprised of 15 genera. The genus Triatoma is the most species-rich and contains important vectors of Trypanosoma cruzi, the causative agent of Chagas disease. Triatoma species were grouped into complexes originally by morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Various studies have established that M. p. longipennis, M. p. picturatus, and M. p. pallidipennis subspecies are almost genetically identical (Martínez et al ., 2005, 2006; Bargues et al ., 2008, Martínez-Hernández et al ., 2010; Espinoza et al , 2013), and pairwise comparisons of ITS-2 sequences indicated identical M. p. longipennis (= T. longipennis ) and M. p. picturatus (= T. picturata ) sequences and only two nucleotide differences between M. p. longipennis, M. p. picturatus, and M. p. pallidipennis (= T. longipennis ). In contrast, other studies of the biological parameters and morphological characteristics have shown important differences among the three subspecies (Martínez-Hernández et al , 2010, Martínez-Ibarra et al , 2012, 2013, 2015 d ; De la Rúa et al ., 2014; Rivas et al ., 2014). Our results are consistent with those last cited studies, supporting the proposal that the three subspecies are different enough from one another to be considered subspecies, not a single one.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have established that M. p. longipennis, M. p. picturatus, and M. p. pallidipennis subspecies are almost genetically identical (Martínez et al ., 2005, 2006; Bargues et al ., 2008, Martínez-Hernández et al ., 2010; Espinoza et al , 2013), and pairwise comparisons of ITS-2 sequences indicated identical M. p. longipennis (= T. longipennis ) and M. p. picturatus (= T. picturata ) sequences and only two nucleotide differences between M. p. longipennis, M. p. picturatus, and M. p. pallidipennis (= T. longipennis ). In contrast, other studies of the biological parameters and morphological characteristics have shown important differences among the three subspecies (Martínez-Hernández et al , 2010, Martínez-Ibarra et al , 2012, 2013, 2015 d ; De la Rúa et al ., 2014; Rivas et al ., 2014). Our results are consistent with those last cited studies, supporting the proposal that the three subspecies are different enough from one another to be considered subspecies, not a single one.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a single marker (or concatenated data from the same mitochondrial genome when two markers were used) on each individual has been particularly problematic. In the general field of systematics, one statistical method for comparing phylogenetic trees, the Shimodaira-Hasegawa Test (Shimodaira and Hasegawa, 1999), has been used extensively (>2,700 citations in ISI Web of Knowledge, May 2016) including several vectors and pathogens (de la Rua et al, 2014; Dyer et al, 2011; Gaunt and Miles, 2002; Hamilton et al, 2007; Outlaw and Ricklefs, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…While nuclear gene trees of species within the T. phyllosoma group have low resolution, they are often regarded as broadly consistent with a priori expectations about species relationships (de la Rúa et al, 2014;Marcilla et al, 2001;Martínez et al, 2006;Mas-Coma & Bargues, 2009). Conversely, the better-resolved mitochondrial trees are regarded as less reliable because of striking mito-nuclear genetree incongruences.…”
Section: Discussionmentioning
confidence: 99%